The Moderating Effect of Performance Management on Operational Control, Technical Control and Telecommunications Systems Performance in the Public Safety Sector of Oman - Khanbashi, Massoud Al-; Aigbogun, Osaro (International Journal of Psychosocial Rehabilitation, 2020)
Many of today’s mission-critical networks in Oman public safety sector face a two-fold challenge. Firstly, modernization of communications infrastructure is required because the present-day requirements for real-time data, sophisticated control as well as monitoring functions surpass the capacity of the existing narrowband networks. Secondly, sustaining real-time communication security is an existing issue, due to the fact that private commercial providers are contracted to handle public safety information coordination, giving them access to sensitive information as well as increased interference. In the Omani context, a change in strategy is required, thus, creating a need for further research to investigate this in a holistic framework. However, this is lacking in the literature and needs to be addressed. In this paper, Technical control and Operational control are independent variables. Performance management is the moderator variable and Telecommunications systems performance is the dependent variable. A quantitative study which employed a self-administered questionnaire for a field survey was carried out on a stratified population of telecommunication users in the Omani public safety sector. Out of a total number of 429 questionnaires administered to the target research population 384 questionnaires were returned and 379 were useable for statistical analysis, which were analyzed using SPSS. After fulfilling assumptions of outlier screening, normality of data distribution and multicollinearity, the quantitative data were subjected to multiple regression analysis, in order to test five research hypothesis. The findings reveal that the direct effect of operational control and performance management on telecommunications system performance was positive and statistically significant, but the direct effect of technical control on telecommunications system performance was not significant. Moreover, it could be concluded that performance management positively moderates the relationship between technical control and telecommunications system performance. Also, that performance management positively moderates the relationship between operational control and telecommunications system performance